2018
DOI: 10.1177/0271678x18757621
|View full text |Cite
|
Sign up to set email alerts
|

Preoperatively reduced cerebrovascular contractile reactivity to hypocapnia by hyperventilation is associated with cerebral hyperperfusion syndrome after arterial bypass surgery for adult patients with cerebral misery perfusion due to ischemic moyamoya disease

Abstract: The present study examined whether preoperatively reduced cerebrovascular contractile reactivity to hypocapnia by hyperventilation is associated with development of cerebral hyperperfusion syndrome after arterial bypass surgery for adult patients with cerebral misery perfusion due to ischemic moyamoya disease. Among 65 adult patients with ischemic moyamoya disease, 19 had misery perfusion in the precentral region on preoperative O positron emission tomography and underwent arterial bypass surgery for that regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…TTP value on a PWI map also verified the improvement of perfusion after RIC, as TTP was always regarded as the preclinical sensitive indicator . RIC may promote the autoregulatory vasodilation and increase oxygen extraction fraction in humans to reduce stroke recurrence rate in chronic cerebral circulation insufficiency . In addition, collateral compensation may contribute to the perfusion improvement, despite with poor evidences of the mechanisms in this study .…”
Section: Discussionsupporting
confidence: 54%
“…TTP value on a PWI map also verified the improvement of perfusion after RIC, as TTP was always regarded as the preclinical sensitive indicator . RIC may promote the autoregulatory vasodilation and increase oxygen extraction fraction in humans to reduce stroke recurrence rate in chronic cerebral circulation insufficiency . In addition, collateral compensation may contribute to the perfusion improvement, despite with poor evidences of the mechanisms in this study .…”
Section: Discussionsupporting
confidence: 54%
“…To define cerebral misery perfusion, PET studies were performed using a SET-3000GCT/M scanner (PET/CT; Shimadzu) for healthy subjects. 29 To detect cerebral misery perfusion, patients underwent the same PET studies more than 3 weeks after the last ischemic event. 29 Before emission scans, a transmission scan (3 minutes) with a 137 Cs point source was performed using a bismuth germanate transmission detector ring coaxially attached to the gadolinium silica oxide emission detector ring.…”
Section: Brain 15 O Gas Pet Studymentioning
confidence: 99%
“…which prevents further cerebral ischemic events. 15,29,30,33 In particular, it is recommended for the symptomatic cerebral hemisphere that shows compromised hemodynamics such as misery perfusion. 11,22 A recent study has demonstrated that although the majority of adult patients undergoing revascularization surgery for MMD show no significant change in cognition compared with their preoperative performance, a small proportion of such patients show apparent improvement in cognition after surgery.…”
mentioning
confidence: 99%
“…To assess cerebral perfusion, a brain N-isopropyl-p-(123I)-iodoamphetamine (IMP) SPECT study was performed using a triple-head gamma camera (GCA-9300R; Toshiba Medical Systems, Tochigi, Japan) [10]. For patients who experienced ischemic symptoms, this study was performed more than 3 weeks after the last ischemic event.…”
Section: Brain Spect and Pet Studiesmentioning
confidence: 99%
“…After intravenous infusion of 222 MBq 123 I-IMP, data acquisition was performed at a mid-scan time of 30 min for a scan duration of 20 min. The SPECT acquisition protocol, post-acquisition processing, and correction were performed as described previously [10]. The brain 123 I-IMP SPECT study was also performed in the same manner 6 months after surgery.…”
Section: Brain Spect and Pet Studiesmentioning
confidence: 99%